Energy populism and household welfare - Cont, Walter Alberto (2009)
We study a cycle of energy prices and estimate its welfare impact on households. A simple framework explains its emergence in terms of the preference of a median household (voter) for receiving transfer gains followed by a future flow of transfer losses. We evaluate actual transfers and welfare effects that a departure of prices of natural gas and electricity generation from opportunity costs since 2003 had on households in the Buenos Aires Metropolitan Region (AMBA) and explore the impact of a way back to opportunity cost pricing.